2005
DOI: 10.1186/1471-2458-5-25
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for treatment delay in pulmonary tuberculosis in Recife, Brazil

Abstract: Background: Tuberculosis is still a great challenge to public health in Brazil and worldwide. Early detection followed by effective therapy is extremely important in controlling the disease. Recent studies have investigated reasons for delays in treatment, but there is no agreed definition of what constitutes an "acceptable" delay. This study investigates factors associated with total delay in treatment of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
3
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 9 publications
10
36
3
23
Order By: Relevance
“…Slightly more women in our study delayed seeking TB care than did men but the difference was not significant. More women than men delayed in a study in Yemen [21]; but not in reports from Armenia and Brazil [24,25]. Patients living in rural areas were significantly more likely to delay than those living in urban areas [26].…”
Section: Discussionmentioning
confidence: 99%
“…Slightly more women in our study delayed seeking TB care than did men but the difference was not significant. More women than men delayed in a study in Yemen [21]; but not in reports from Armenia and Brazil [24,25]. Patients living in rural areas were significantly more likely to delay than those living in urban areas [26].…”
Section: Discussionmentioning
confidence: 99%
“…The radiographic manifestations of TB/HIV co-infection depend on the degree of immunosuppression. In those individuals with CD4 counts ture (after CT evaluation) shows the following: pleocytosis (rarely > 1,000 cells/mm 3 ); leukocyte counts ranging from 100 to 500/mm 3 , with a predominance of lymphocytes; high protein levels (100 to 500 mg%); and low glucose levels (< 40 mg%). The differential diagnosis should be causes of lymphocytic meningitis, and clinical suspicion, epidemiological history, and evaluation of the immunological status of the patients are essential.…”
Section: Diagnosis Of Extrapulmonary Tbmentioning
confidence: 99%
“…Previous studies have shown that a delay in diagnosis is closely related to poor access to health care 8,9 . Despite TB control programs' recommendation that diagnosis should be made at the primary health care level, most patients are still diagnosed in hospitals.…”
Section: Introductionmentioning
confidence: 99%